Managing the multibusiness company : strategic issues for diversified groups (Routledge, 1996)
This book is about: Economic justification for the multibusiness firm; Resource allocation and portfolio composition; The quest for synergy; Diversification, performance and restructuring; How corporate parents influence their businesses; and Developing a corporate strategy.